Pelatihan E-Learning Moodle Berbasis Cloud Untuk Tutor/Guru Pusat Kegiatan Belajar Masyarakat (PKBM) - Albaar Rubhasy; Raden Muhammad Firzatullah; Riad Sahara (Terang, 2021)
The Community Learning Activity Center (PKBM) is a non-formal education unit that provides educational services for people in need. Currently PKBM uses face-to-face learning methods in classrooms, so it is not optimal for learning citizens because interaction with tutors can only be done in the PKBM environment. On the other hand, e-learning technology can make it easier for PKBM tutors / teachers in implementing learning because learning can be done anytime and anywhere according to the abilities of the teaching participants. The main objective of this community service activity is to provide training in the use of cloud-based Moodle e-learning for PKBM tutors / teachers. The implementation methods consist of: (1) Needs Analysis; (2) CloudMoodle implementation; (3) Preparation of Training Materials; (4) Data Collection of Prospective Training Participants; (5) Creating PKBM Tutor / Teacher Accounts; and (6) Evaluation and Reporting. The training was attended by 31 participants from 10 PKBM institutions. The training material is delivered interactively with materials including: (i) a general explanation of the Moodle application; (ii) learning material management training; and (iii) Value management training. Based on the results of the evaluation, the training activities were well organized based on the feedback given by the participants in terms of three aspects: (i) the participants' understanding of the training material; (ii) providing training; and (iii) training resource persons.